2012
DOI: 10.1016/j.jalgebra.2011.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Group actions on algebras and the graded Lie structure of Hochschild cohomology

Abstract: Hochschild cohomology governs deformations of algebras, and its graded Lie structure plays a vital role. We study this structure for the Hochschild cohomology of the skew group algebra formed by a finite group acting on an algebra by automorphisms. We examine the Gerstenhaber bracket with a view toward deformations and developing bracket formulas. We then focus on the linear group actions and polynomial algebras that arise in orbifold theory and representation theory; deformations in this context include grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 23 publications
5
46
0
Order By: Relevance
“…Next we generalize [23,Theorem 8.7] to fields of arbitrary characteristic (see also [25,Theorem 11.4…”
Section: Since [λ λ] = 2dmentioning
confidence: 99%
“…Next we generalize [23,Theorem 8.7] to fields of arbitrary characteristic (see also [25,Theorem 11.4…”
Section: Since [λ λ] = 2dmentioning
confidence: 99%
“…Representations and homological properties of skew group algebras (or more generally, group-graded algebras and crossed products) have been widely studied; see [5,7,16,[19][20][21]27]. When |G|, the order of G, is invertible in k, it has been shown that ΛG and Λ share many common properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the lemma below, we give a formula for the ϕ‐circle product of special types of elements. Our formula may be compared with [, Lemma 4.1; , Theorem 7.2]. Due to the structure of the Hochschild cohomology of S(V)#G stated in Proposition , this formula will in fact suffice to compute all brackets.…”
Section: ϕ‐Circle Product Formula and Projections Onto Group Componentsmentioning
confidence: 99%
“…In Corollary we also show that the Hochschild cohomology prefixHHfalse(S(V)#Gfalse) is a graded Gerstenhaber algebra with respect to a certain natural grading coming from the geometry of the fixed spaces Vg, which we refer to as the codimension grading. Section 6 consists of examples and a general explanation of (non)vanishing of the Gerstenhaber bracket for S(V)#G, rephrasing some of the results of .…”
Section: Introductionmentioning
confidence: 99%